Magnetic resonance imaging measures of brain atrophy from the EXPEDITION3 trial in mild Alzheimer's disease - Adam J. Schwarz; Karen L. Sundell; Arnaud Charil; Michael G. Case; Ralf K. Jaeger; David Scott; Luc Bracoud; Joonmi Oh; Joyce Suhy; Michael J. Pontecorvo; Bradford C. Dickerson; Eric R. Siemers (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Solanezumab is a humanized monoclonal antibody that preferentially binds to soluble amyloid β and promotes its clearance from the brain in preclinical studies. The objective of this study was to assess the effect of solanezumab in slowing global and anatomically localized brain atrophy as measured by volumetric magnetic resonance imaging (MRI). Methods In the EXPEDITION3 phase 3 trial, participants with mild Alzheimer's disease were randomized to receive intravenous infusions of either 400 mg of solanezumab or placebo every 4 weeks for 76 weeks. Volumetric MRI scans were acquired at baseline and at 80 weeks from 275 MRI facilities using a standardized imaging protocol. A subset of 1462 patients who completed both MRI and 14‐item Alzheimer's Disease Assessment Scale–Cognitive Subscale assessments at both time points were selected for analysis. Longitudinal MRI volume changes were analyzed centrally by tensor‐based morphometry with a standard FreeSurfer brain parcellation. Prespecified volumetric measures, including whole brain and ventricles, along with anatomically localized regions in the temporal, parietal, and frontal lobes were evaluated in those participants. Results Group‐mean differences in brain atrophy rates were directionally consistent across a number of brain regions but small in magnitude (1.3–6.9% slowing) and not statistically significant when corrected for multiple comparisons. The annualized rates of change of the volumetric measures and the correlation of these changes with cognitive changes in placebo‐treated subjects were similar to those reported previously. Discussion In the EXPEDITION3 trial, solanezumab did not significantly slow down rates of global or anatomically localized brain atrophy. Brain volume changes and their relationship to cognition were consistent with previous reports.